The role of students in anti-bullying efforts in the educational enviroment - Lestari, Sely Ayu; Laili, Innayatul (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
Many children who experience intimidation find that school they is environment that is not friendly, However protection rights civil to abuse only applicable for children included in protected classes, such as group race and ethnicity minority, students sufferer disabilities, and victims of abuse gender or discrimination religion. Study This use method research qualitative descriptive with source informant from from students of Wiranegara PGRI University. Research results This show that There is three relevant criteria For define behavior aggressive as oppression: (1) repetition, (2) intention, and (3) imbalance power. Ways of dealing with and preventing it carried out by students covering socialization and dissemination information through social media. Bullying involving interaction dynamic between perpetrators and victims. Power perpetrator intimidation increased, and power victim even reduce. As a result, difficult for victim for respond or overcome the problem. Oppression consists of from attack verbal (for example name calling, threats), behavior physical (eg. hit, kick, damage victim's property), And aggression relational / social (for example exclusion social, distribution rumors) until form attack latest through the Internet and technology new (also called as cyberbullying).